2021
DOI: 10.3390/educsci11100579
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Teaching–Learning Methods (ETLM) during COVID-19: Lessons Learned from Sri Lanka

Abstract: Sri Lanka’s education system was suddenly shifted from classroom-based free education to online-based distance learning as an emergency teaching and learning method (ETLM) in response to the COVID-19 pandemic lockdown. This study examines how various stakeholders used online-based distant learning as an ETLM, and highlights the lessons learned from such a transition in Sri Lanka through a case study of the Kandy education zone (KEZ), in response to the country’s COVID-19 pandemic lockdown. We obtained the data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 22 publications
1
7
0
1
Order By: Relevance
“…The fourth emergent sub-theme arising from the challenges is students' engagement and level of understanding. The result is in line with the works of Dhawan (2020); Gangahagedara et al (2021); Sangster et al (2020); Valsaraj et al (2021) where it is the utmost challenge faced by most educators in this study. During online classes, educators need to deal with a large number of students; thus, it is difficult to ensure all students' engagement during class session.…”
Section: Findings and Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The fourth emergent sub-theme arising from the challenges is students' engagement and level of understanding. The result is in line with the works of Dhawan (2020); Gangahagedara et al (2021); Sangster et al (2020); Valsaraj et al (2021) where it is the utmost challenge faced by most educators in this study. During online classes, educators need to deal with a large number of students; thus, it is difficult to ensure all students' engagement during class session.…”
Section: Findings and Discussionsupporting
confidence: 90%
“…Most universities are not physically and technologically prepared for fully online teaching. Many educators are minimally trained, and few have fully embraced the online learning mode (Gangahagedara et al, 2021;Nasu, 2020;Sangster et al, 2020). Therefore, many faculties pursue training for the online delivery of lectures because most of their educators are using the online learning platforms as the delivery tool during the pandemic (Colpitts et al, 2020;Valsaraj et al, 2021).…”
Section: Literature Review Emergency Remote Teaching (Ert)mentioning
confidence: 99%
See 1 more Smart Citation
“…Estos resultados, coincidentes con algunos estudios (Jiménez-Hernández et al, 2020;Pérez-López et al, 2021;Totlis et al, 2021), ponen de manifiesto que, a pesar de la apuesta de organismos nacionales por la renovación pedagógica y la adaptación de la docencia al contexto COVID-19, el modelo de aprendizaje dirigido todavía continúa siendo el más prevalente. Contrariamente, diversas investigaciones derivadas del COVID-19 han concluido que, el uso metodológico, se ha transformado significativamente como consecuencia del paso de un modelo de enseñanza presencial a otro virtual o semipresencial (Barlovits et al, 2021;Collado-Valero et al, 2021;Gangahagedara et al, 2021;Latorre-Cosculluela et al, 2021;Vizcaya-Moreno & Pérez-Cañaveras, 2020).…”
Section: Discusión Y Conclusionesunclassified
“…Weerathunga et al [8] has reported an increase in the acceptance ratio of E-Learning among the university students and teachers as a reliable way to continue education during the extreme situation as the COVID-19 pandemic. Several universities have reported an apparent motivational factor from including these e-learning techniques in the educational pedagogical strategies pool [9,10]. This effect is a significant positive, and fights against the depression and mental disorder cases increased related to COVID-19 isolation or family loss [11].…”
Section: Introductionmentioning
confidence: 99%